Comparative Analysis of the Status and Influencing Factors of Immunization Among Children Between Registered and Floating Population - Xiong, Yan; Xue, Yaqing; Jiao, Guojin; Xie, Jun; Cheng, Jingmin (Frontiers in Public Health, 2022)
Background: Vaccine is an effective tool to reduce the gap between the rich and the poor and improve health equity, through which a number of serious childhood diseases can be successfully prevented or eradicated. This study aimed to compare the current situation of vaccination and related factors among children in China’s registered residence and floating population, so as to provide reference for achieving the 100% vaccination rate in China. Methods: The data used for this study are from the 2017 National Migrants Dynamic Monitoring Special Survey data. A self-designed questionnaire was used to collect information on registered population and floating population, including socio-demographics, vaccination status of children and so on. Descriptive statistics and chi-square independence test were used to describe the information and to compare the vaccination status of children under different sociodemographic characteristic. Binary logistic regression was employed to analyze influencing factors associated with children vaccination. Results: The findings showed that 94.39% of children in registered residence were completely vaccinated, which was significantly higher than that of the floating children (91.68%, P<0.001). Region, parents’ education level and marital status were found to be significant risk factors for complete vaccination of children regardless of the registered or floating population. In addition, ethnicity and length of time to nearest medical institution were unique risk factors for complete vaccination of children in registered residence. And health record was an independent influencing factor for vaccination of children of floating population. Conclusion: Compared with registered population, floating population was at a disadvantage in using basic public health services, especially in children’s vaccination. To achieve 100% vaccination for children, particular interventions should be taken for different populations.